Weakly Supervised Slot Tagging with Partially Labeled Sequences from Web Search Click Logs - Kim, Young-Bum; Sarikaya, Ruhi (North American Chapter of the Association for Computational Linguistics (NAACL), 2015)
In this paper, we apply a weakly-supervised learning approach for slot tagging using conditional random fields by exploiting web search click logs. We extend the constrained lattice training of Tackstrom et al. (2013) to ¨ non-linear conditional random fields in which latent variables mediate between observations and labels. When combined with a novel initialization scheme that leverages unlabeled data, we show that our method gives significant improvement over strong supervised and weakly-supervised baselines.